Pengaruh Intensitas Menonton Konten Iwil Spill The Tea di Youtube Terhadap Kepercayaan Informasi dan Penyebaran Gosip di Media Sosial - NandaTassya Wildan; Riswandi Riswandi (SCIENTIA JOURNAL, 2026)
YouTube has transformed the way people access information and interact virtually, and among the many creators producing gossip-related content is a popular podcast channel, Iwil Spill The Tea. The content, themed around the trending phrase “Spill The Tea,” has become synonymous with gossiping. This study aims to analyze the influence of viewing intensity of the Iwil Spill The Tea content on information trust and gossip dissemination. Data were collected from the community through field surveys using a stratified random sampling method. The data were analyzed quantitatively and qualitatively with descriptive techniques, supported by SPSS version 26 using simple linear regression. The results show that viewing intensity significantly influences information trust, with a significance value of 0.003 < 0.05. Furthermore, viewing intensity also has a significant effect on gossip dissemination, with a significance value of 0.039 < 0.05. These findings indicate that the more frequently individuals watch the content, the higher their level of trust in the information presented and the greater their confidence in sharing gossip-related information with others.